ANALISIS YURIDIS PEMBERIAN HAK TANGGUNGAN PADA HAK MILIK SATUAN RUMAH SUSUN BERDASARKAN UNDANG-UNDANG NOMOR 20 TAHUN 2011 TENTANG RUMAH SUSUN - SYAHNIDA MAHARANI (PREMISE LAW JURNAL, 2014)
ABSTRACT Giving hypothecation is a burden for land rights and other properties related to the land, particularly for the ownership of apartment buildings as its objects which are used as the guarantee for paying off a certain debt; it is implemented based on the prevailing regulations such as Law No. 4/1996 on Hypothecation, Law No. 20/2011 on Apartment Buildings and other Regulations Related to the Giving Hypothecation to The Ownership of The Apartment Building Units. The process of giving it is preceded by making loan agreement as the main agreement and followed by the signing of APHT made by a Notary empowered to draw up land deeds, according to the regulation of the Head of the National Land Office No. 8/2012, followed by registering it in the local land Office which issues Hypothecation Certificate which has executorial legal force when the debtor breaches the contract. Keywords:  Hypothecation, Ownership of Apartment Building Units, Execution